Color shift acceleration on mid-power LED packages. (November 2017) - Lu, Guangjun; van Driel, W.D.; Fan, Xuejun; Fan, Jiajie; Qian, Cheng; Zhang, G.Q.
Abstract: Mid-power LED packages are now widely used in many indoor illumination applications due to several advantages. Temperature stress, humidity stress and current stress were experimentally designed and performed to accelerate the color shift of mid-power LED packages and color shift mechanisms have been discussed based on the color shift results obtained from measurements. Conclusions could be drawn: - Linear function fitting demonstrates a good linear relationship between color shift (Δu′ Δv′) and aging time almost for all the aging conditions. We can extrapolate the color shift Δu′ and Δv′ based on the fitted regression equations and then make the prediction for the total color shift Δu′v′. - Current stress can induce a different failure mode. Peak intensity reduction analysis reveals that the current stress accelerates the degradation of LED die. - Humidity test induced a substantial color shift both in u′ and v′. The u′ has an increased degradation rate after aging of 3000 h at 85%RH & 85 °C, there should be different degradation mechanisms during the whole humidity test. The molecular structure decomposition of silicone plates and then follows the silicone carbonization due to the long-term (3000 h) accumulated high localized temperature aging. Highlights: Linear function fitting demonstrates a good linear relationship between color shift and aging time. The lifted junction temperature induced by the current will further reduce blue light peak intensity. The molecular structure decomposition of silicone plates and then follows the silicone carbonization.